2021
DOI: 10.47191/ijsshr/v4-i3-30
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Creative Problem Solving Learning Models on Problem Solving Ability in Learning Motivation and Student Self-Efficacy View

Abstract: This study aims to determine; 1) the effect of using creative problem-solving learning models on mathematical problem-solving abilities, 2) the influence of learning motivation on mathematical problem-solving abilities, 3) the influence of students' self-efficacy on mathematical problem-solving abilities, 4) interactions between creative problem-solving learning models with students' learning motivation towards mathematical problem-solving abilities, 5) interaction between creative problem-solving learning mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Research conducted by Kim et al (2019) related to CPS showed that there was a significant increase in various measures of creativity, creative problem solving, and character. The CPS model is more effective in influencing problem solving abilities than conventional learning (Hobri et al, 2020;Baity, 2021). CPS supports permanent and meaningful learning (Tseng et al, 2013) outcomes and creativity because it provides opportunities to discover concepts and construct knowledge independently (Kristanti et al, 2018).…”
Section: Critical Thinkingmentioning
confidence: 99%
“…Research conducted by Kim et al (2019) related to CPS showed that there was a significant increase in various measures of creativity, creative problem solving, and character. The CPS model is more effective in influencing problem solving abilities than conventional learning (Hobri et al, 2020;Baity, 2021). CPS supports permanent and meaningful learning (Tseng et al, 2013) outcomes and creativity because it provides opportunities to discover concepts and construct knowledge independently (Kristanti et al, 2018).…”
Section: Critical Thinkingmentioning
confidence: 99%